PENDAMPINGAN DIGITALISASI UMKM DESA SUNGGINGAN GUNUNG KIDUL - Widyayanti, Evi Rosalina; Zulkifli, Zulkifli; Setyawati, Rufaida; Yulianti, Eka Nur; Khasanah, Yuliani Nuril; Naya, Dea Arun; Putri, Rayhana Syauqi (BESIRU : Jurnal Pengabdian Masyarakat, 2025)
This Community Service Program aims to increase the capacity and competitiveness of MSMEs in Sunggingan Village through assistance in utilizing digital technology. The problems faced by MSMEs in this village are, first, the lack of understanding of digital finance and minimal knowledge about transaction security in the digital era. Second, the less than optimal use of digital platforms to expand the reach of local product marketing. The implementation method is divided into three, namely socialization, counseling and practice for MSMEs with businesses such as culinary, services (laundry, sewing), agriculture, livestock, furniture, and grocery and basic necessities businesses that have broad market potential. This Community Service Program has met the target and achievement of service. It is hoped that the results obtained can continue to be developed for the success of future MSME actors to be better and able to manage finances more wisely using sophisticated digital technology.